2021
DOI: 10.3390/ijms22020762
|View full text |Cite
|
Sign up to set email alerts
|

Impressic Acid Attenuates the Lipopolysaccharide-Induced Inflammatory Response by Activating the AMPK/GSK3β/Nrf2 Axis in RAW264.7 Macrophages

Abstract: Inflammatory diseases are caused by excessive inflammation from pro-inflammatory mediators and cytokines produced by macrophages. The Nrf2 signaling pathway protects against inflammatory diseases by inhibiting excessive inflammation via the regulation of antioxidant enzymes, including HO-1 and NQO1. We investigated the anti-inflammatory effect of impressic acid (IPA) isolated from Acanthopanax koreanum on the lipopolysaccharide (LPS)-induced inflammation and the underlying molecular mechanisms in RAW264.7 cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…2020). This plant is mainly distributed in China, North Korea, Japan, and Russia ( Kawano et al, 2021 ), and related studies have confirmed that it has multiple pharmacological benefits, such as anti-neuroinflammation, antibacterial, anti-cancer ( Kim et al, 2018 ; Kawano et al, 2021 ), anti-inflammatory ( Lee et al, 2021 ), anti-oxidation ( Kim et al, 2015 ), anti-AChE, and anti-BuChE features ( Li et al, 2021 ). Additionally, it has positive effects on the cardiovascular ( Jin et al, 2020 ), central nervous, and immune systems ( Jia et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…2020). This plant is mainly distributed in China, North Korea, Japan, and Russia ( Kawano et al, 2021 ), and related studies have confirmed that it has multiple pharmacological benefits, such as anti-neuroinflammation, antibacterial, anti-cancer ( Kim et al, 2018 ; Kawano et al, 2021 ), anti-inflammatory ( Lee et al, 2021 ), anti-oxidation ( Kim et al, 2015 ), anti-AChE, and anti-BuChE features ( Li et al, 2021 ). Additionally, it has positive effects on the cardiovascular ( Jin et al, 2020 ), central nervous, and immune systems ( Jia et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%